THE ORAL TOLERANCE TO CONTACT ALLERGENS IN PROSTHODONTIC BIOMATERIALS. Case reports - Iliyana Stoeva (Peytchinski Publishing, 2010)
Two cases of oral allergy to dental prosthodontic materials are presented, highlighting the interest of dosage of allergen and the clinical manifestation of contact allergy to prosthodontic dental materials. Symptoms appeared after placement of a new prosthesis of same material as the precedent one. These patients were able to tolerate the allergen in minor quantity and the increasing of the quantity interrupt the tolerance. These cases indicate a possible relationship between the oral contact allergy and the dosage of the allergen.